“Anak Nagari” dan Kekuasaan: Relasi Kekuasaan Informal Dalam Konflik Penguasaan Sumber Ekonomi Di Kecamatan Pauh - Redho Rama Putra; Asrinaldi Asrinaldi; Afrizal Afrizal (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This study discusses the emergence of client protection groups and power relations in the